Harnessing Heterogeneous Wrinkles in Metal/Polydimethylsiloxane Film System by Combination of Mechanical Loading and Heat Treatment. Issue 9 (11th March 2020) - Lu, Chenxi; Yu, Senjiang; Li, Huihua; Zhou, Hong; Jiao, Zhiwei; Li, Lingwei
Abstract: Spontaneous wrinkled surfaces in nature usually possess unique physical and chemical properties. Inspired by nature and stimulated by practical application, artificial wrinkle patterns have received increasing interest recently. Here, the controllable heterogeneous wrinkles in metal films deposited on polydimethylsiloxane substrates by combination of mechanical loading and heat treatment is reported. It is found that the wrinkles are spontaneously localized at small strain condition due to the uneven distribution of wrinkle amplitudes on the film surface. The morphological features and underlying mechanisms of such wrinkles are investigated based on the strain theory. The friction property is found to be well controlled by the aspect ratio and orientation of the wrinkle patterns. Complex 2D wrinkle array is also achieved by applying heat treatment and mechanical compression in sequence. This study may broaden the knowledge of spontaneous heterogeneous wrinkles in film‐substrate system and provide a novel way to tailor various wrinkle patterns via independently tuning annealing temperature and mechanical strain. Abstract : The controllable formation of heterogeneous wrinkles in silver films sputter deposited on polydimethylsiloxane substrates by combination of mechanical loading and heat treatment is presented. The friction property of 1D heterogeneous wrinkles exhibits strong anisotropy and good tunability. This study can provide a novel way to tailor various 2D wrinkle patterns via independently tuning annealing temperature and mechanical strain.